Nonstationary flow of roiling liquid - Hai, Duong Ngoc (Vietnam Journal of Mechanics, 1984)
Steady one-dimensional nonstationary flow of boiling liquid from finite or infinit pipe in a consideration of the effect of the phase-boundary heat and mass transfer. The Received system of quasi-linear differential equations has been decided by the modificati on of Lax - wendroff method in IBM. Numerical results are compared as xperimental data.